Financial Inclusion through Mobile Banking: Evaluating the Impact of Digital Payment Systems in Kenya - David Kamau Njoroge (Mustard Journal De Ecobusin, 2025)
This study examines the position of mobile banking in improving financial inclusion in Kenya with specific focus on how the adoption of mobile banking impacts on access to financial products, financial behaviors and economic participation in general. The cross-sectional quantitative research design was used, where information was collected on the 450 adult respondents in the urban and rural areas of Kenya. The data was interrogated using descriptive statistics, chi-square tests, regression analysis, and t-tests. The research results show that mobile banking consumers have far more access to savings, credit, and insurance services than non-users. In addition, the greater the adoption of mobile banking, the greater the positive correlation with the enhanced financial behavior, which includes increased saving and borrowing. Demographic characteristics such as age, the income level, and the level of education were identified to have a considerable effect on the adoption of mobile banking, and gender was not found to have a similar effect. The major challenges which were identified to include the security apprehension and lack of awareness were identified as key barriers to adoption. All in all, the findings highlight the potential of mobile banking to advance financial inclusion, and at the same time, should point to the areas in which specific interventions can be used to increase access to mobile financial services by underserved populations.